2013
DOI: 10.1080/1612197x.2013.839413
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Adolescent health through an intervention aimed at improving the quality of their participation in Physical Activity (PAPA): Background to the project and main trial protocol

Abstract: International audienceFunded by the European Commission, the Promoting Adolescent health through an intervention is aimed at improving the quality of their participation in Physical Activity (PAPA) project revolved around the potential of youth sport to promote children's mental and emotional health and physical activity engagement. A theoretically grounded coach education training programme (i.e. Empowering CoachingTM), which was designed to create a sporting environment which was more positive and adaptive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 22 publications
0
46
0
11
Order By: Relevance
“…In contrast to the reporting at the individual-level, a single trial12 20 30 assessed maintenance among educators conducting the CDP and compared those who did and did not maintain their use of the CDP over time. Still, none of the trials reported whether or not a CDP was used by sport organisations at later points in time or was institutionalised (eg, related to changes in organisational values).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the reporting at the individual-level, a single trial12 20 30 assessed maintenance among educators conducting the CDP and compared those who did and did not maintain their use of the CDP over time. Still, none of the trials reported whether or not a CDP was used by sport organisations at later points in time or was institutionalised (eg, related to changes in organisational values).…”
Section: Resultsmentioning
confidence: 99%
“…No estuvieron presentes los entrenadores ni los directivos de los clubes, y al menos un investigador estuvo presente durante la administración. Para una descripción del protocolo y del procedimiento véase Duda et al (2013). Los datos fueron recogidos en octubre-diciembre de la temporada 2011/2012.…”
Section: Procedimientounclassified
“…Via the Promoting Adolescent Physical Activity 450 (PAPA) project (seeDuda et al, 2013), Duda and colleagues revealed that football coaches at end of the season (i.e., 7 months post workshop), for coaches who attended457 Empowering Coaching™(Smith et al, 2015b). The benefits of Empowering Coaching TM 458 also extended to the athletes; findings from the PAPA project revealed that players whose 459 coaches attended the Empowering Coaching TM training reported decreased in their intentions 460 to drop-out of football during the season (compared to players whose coaches did not receive 461 the training)(Quested et al, 2015).…”
mentioning
confidence: 97%